Asia-Pacific Countries with Special Needs Development Report 2020 - United Nations Economic; Social Commission for Asia; the Pacific (United Nations)
This annual ESCAP publication discusses issues of interest for Asia-Pacific least developed countries (LDCs), landlocked developing countries (LLDCs) and small island developing States (SIDS), collectively referred to as countries with special needs (CSN). The 2020 edition of the report offers analytical studies and policy recommendations for Pacific SIDS to successfully manage their vast ocean resources and, in turn, maintain healthy blue economy sectors, such as coastal fisheries and marine-based tourism. As these States are otherwise limited in their land-based resources, making better use of the blue economy could provide valuable employment and sustenance for local populations and, ultimately, the means for achieving the Sustainable Development Goals. To that end, this report emphasizes the importance of greater regional cooperation in the creation of an enabling framework, especially given the nature of fisheries as a common property resource.